2020
DOI: 10.1016/j.jaccas.2020.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade in a Patient With Myocardial Infarction and COVID-19

Abstract: . We present the case of a patient with myocardial infarction and COVID-19 infection who developed hemorrhagic pericardial effusion and cardiac tamponade. The differential diagnosis included postinfarction pericarditis and mechanical complications, thrombolysis, Dressler´s syndrome and viral pericarditis. The histopathological examination of the pericardial tissue sample and electron microscopy established the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 2 publications
0
22
0
2
Order By: Relevance
“…The presence of COVID-19 in pericardial fluid has been recently reported [26]. Also, viral particles in pericardial effusion were seen on electron microscopy [27]. From our standpoint, this is a sufficient reason to include early echocardiography into the standard work-up of symptomatic COVID-19 patients.…”
Section: Discussionmentioning
confidence: 55%
“…The presence of COVID-19 in pericardial fluid has been recently reported [26]. Also, viral particles in pericardial effusion were seen on electron microscopy [27]. From our standpoint, this is a sufficient reason to include early echocardiography into the standard work-up of symptomatic COVID-19 patients.…”
Section: Discussionmentioning
confidence: 55%
“…Also in Foster et al study of a 44-year-old woman reveal a positive COVID-19 test three weeks before her large hemorrhagic pericardial effusion (with a two-week isolation period)(13). Cruz et al reported another hemorrhagic pericardial effusion and cardiac tamponade on the ninth day of the illness 14 . In addition to the above, Purohit et al presented an 82-year-old woman with five days of productive cough, fever with chills, and intermittent diarrhea.…”
Section: Review Of Literaturementioning
confidence: 98%
“…COVID-19 testing on the pericardial fluid is neither available widely nor validated. However, COVID-19 has been demonstrated in the pericardial fluid using reverse transcriptase-polymerase chain reaction and electron microscopy [ 14 , 15 ]. Since management would not change depending on this, it is reasonable to avoid these investigations, which are often laborious and expensive.…”
Section: Discussionmentioning
confidence: 99%